2001
DOI: 10.1021/bi001654n
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Protein Kinase C Isozymes with Rho GTPases

Abstract: Evidence is provided for direct protein-protein interactions between protein kinase C (PKC) alpha, betaI, betaII, gamma, delta, epsilon, and zeta and members of the Rho family of small GTPases. Previous investigations, based on the immunoprecipitation approach, have provided evidence consistent with a direct interaction, but this remained to be proven. In the study presented here, an in vitro assay, consisting only of purified proteins and the requisite PKC activators and cofactors, was used to determine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 50 publications
(85 reference statements)
8
73
0
Order By: Relevance
“…Since some Gq coupled receptors have been reported to also interact with G 12/13 signaling [38][39][40][41], it is conceivable that G 12/13 signaling is activated following P2Y 6 receptor stimulation. It was also shown that Rho signaling activated PKCs [18,42,43]. These findings suggest that the activation of Rho and PKC is induced by P2Y 6 receptor activation and regulates F-actin aggregation.…”
Section: Udp-induced Vasp Phosphorylation At Ser157 Is Mediated By Rhmentioning
confidence: 81%
See 1 more Smart Citation
“…Since some Gq coupled receptors have been reported to also interact with G 12/13 signaling [38][39][40][41], it is conceivable that G 12/13 signaling is activated following P2Y 6 receptor stimulation. It was also shown that Rho signaling activated PKCs [18,42,43]. These findings suggest that the activation of Rho and PKC is induced by P2Y 6 receptor activation and regulates F-actin aggregation.…”
Section: Udp-induced Vasp Phosphorylation At Ser157 Is Mediated By Rhmentioning
confidence: 81%
“…We examined the involvement of Rho GTPases because it was reported that PKC was a downstream target of RhoA [18] and VASP phosphorylation was regulated by RhoA activation [19]. We use the Rho inhibitor CT04 to inactivate RhoA, RhoB and RhoC.…”
Section: Udp-induced Actin Aggregation and Vasp Phosphorylation Were mentioning
confidence: 99%
“…The Rho family and their upstream or downstream factors have been implicated in various cellular functions such as regulation of actin filament reorganization and exocytosis (27,28). In mast and chromaffin cells, one or more members of the Rho family play an active role in the exocytotic process (27,28,59,60).…”
Section: Discussionmentioning
confidence: 99%
“…In mast and chromaffin cells, one or more members of the Rho family play an active role in the exocytotic process (27,28,59,60). In addition, Cdc42 and Rac control regulated secretion in pancreatic ␤-cells (61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation